Rapid mixed lymphocyte culture testing by analysis of the insulin receptor on alloactivated T lymphocytes: implications for human tissue typing. - Helderman, J H (1981)
Responses in the mixed lymphocyte culture (MLC) are traditionally evaluated by measurement of DNA synthesis or blast transformation. However, these events occur too late in the MLC to permit prospective matching for cadaveric renal transplantation. Presentation of allogeneic cells to the T lymphocyte within the MLC results in the emergence of an insulin receptor pharmacokinetically similar to that on other tissues such as fat, liver, and muscle. Intrafamilial MLC were studied by simultaneous assessment of DNA synthesis and insulin receptor binding. In 68 studies from seven families that provide examples of two haplotype identical matches, haplo-identical matches and total haplo mismatches, the presence of an insulin receptor correlated in every case with a positive MLC as estimated by [3H]thymidine incorporation. A quantitative relationship existed between the strength of the MLC and the amount of receptor binding. Based on analysis of cells from several families in which crossover events were known to have occurred, the appearance of an insulin receptor always corresponded with a mismatch at the portion of histocompatibility leukocyte antigen (HLA) chromosome bearing the D region. Finally, it was demonstrated in each of 30 cultures that insulin receptor emergence occurred significantly before detectable DNA synthesis, as early as 24 h after the initiation of the MLC, well within the time-constraint limitations for renal preservation. Appearance of the insulin receptor on activated lymphocytes may be a more rapid measure of mixed lymphocyte responses, and should permit prospective matching for cadaveric renal transplantation.